AN ANALYSIS OF SALES INFORMATION SYSTEM AND COMPETITIVE ADVANTAGE (Study Case of UD. Citra Helmet) - Alianto, Hendra; Wijaya, Santo Fernandi; Arlan, Fikri (Bina Nusantara University, 2012)
Business development in this era of globalization leads companies to use information system in running business relationship by changing the traditional way of working in non-integrated information systems into integrated information systems. The intended use of the integrated information system will improve the effective and efficient way of working, such as the availability of information in real-time, accurate and informative for decision-making for the benefit of operational activities, as well as decision-making for strategic interests and the company’s business development. Especially with the application of sales information system, it will improve the company’s performance and will affect the competitiveness of companies, which can ultimately increase the maximum profit. However, in reality it is not easy to implement the integrated information system, because it is influenced by the customs, culture and mindset of the user company. It is necessary for running system analysis activity and building an integrated information system by concerning into the needs of users, management, customers and stakeholders. The implementation of integrated information system will increase productivity and achieve the effectiveness and efficiency level of company’s operations, through the analysis of sales information system will affect the competitiveness of companies.Keywords: Sales Information System Analysis